Tongqiao Huoxue Decoction for the treatment of acute ischemic stroke: A Systematic Review and meta-analysis. (30th January 2022) - Zhou, Xiu; Shao, Tianyu; Xie, Xiuzhen; Ding, Minrui; Jiang, Xumin; Su, Pingping; Jin, Zhuqing
Abstract: Ethnopharmacological relevance: The aim of this study was to evaluate the efficacy and safety of Tongqiao Huoxue Decoction (TQHXT) in the treatment of acute ischemic stroke (AIS); Study Design: A total of 17 randomized controlled trials, involving 1489 AIS patients, were included for data analyses. Materials and methods: All randomized controlled trials (RCTs) of TQHXT in the treatment of acute ischemic stroke before September 2020 were retrieved from seven electronic databases, including PubMed, Web of Science, Central, CNKI, CBM, Wanfang, and VIP. Data were analyzed by RevMan 5.3 software, and quality was evaluated by GRADEpro; Results: Results showed that, while TQHXT demonstrated undeniable positive effects in clinical effective rate, neurological deficit scores, activities of daily living (ADL) scores, and hemorheology (including HCT; fibrinogen; plasma viscosity and platelet adherence rate), adverse events (AE) require further study; and Conclusions: This study provides evidence that TQHXT is an effective treatment for acute ischemic stroke. However, due to the limited quality of the included studies, the above conclusion needs to be further verified by stricter randomized controlled, double-blind, large-sample, high-quality trials. Graphical abstract: Image 1 Highlights: Data obtained from 17 trials with 1489 subjects (745/744) were meta-analyzed. TQHXT demonstrated positive effects in clinical effective rate and hemorheology. TQHXT reduced neurological deficit scores, activities of ADL scores. Adverse events require further study.